SIMULATION AND EXPERIMENTAL RESEARCH OF ELECTRIC POWER STEERING SYSTEM BASED ON MULTI-BODY DYNAMICS - LI Cheng; LI Min; WANG AiGuo; CHENG Yu (Jixie qiangdu)
By collecting the hard points data of an independent brand electric vehicle, EPS dynamic model was established and the assistance characteristic parameters of the model were designed. The steering simulation test was carried out by using ADAMS software. The accuracy of the model was verified. Relationship between steering wheel input torque and EPS output torque were compared and analyzed under different conditions with and without assistance. Finally, the real vehicle road test and Adams vehicle simulation were used. The steering wheel middle position handling stability test was carried out. The test results show that the EPS system is reasonably designed and has good handling and stability under high-speed driving conditions.